Pengaruh Tax Avoidance Terhadap Nilai Perusahaan dengan Kebijakan Deviden sebagai Variabel Moderasi Sektor Energi yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023 - Cinta Rosa N Girsang; Anissa Yuniar Larasati (Ekonomis: Journal of Economics and Business, 2026)
This study aims to examine the effect of tax avoidance on firm value by considering the role of dividend policy as a moderating variable. The study sample consists of energy sector companies listed on the Indonesia Stock Exchange during the 2019–2023 period. The research method used is a quantitative approach with Moderated Regression Analysis (MRA) analysis techniques. The results show that tax avoidance has no significant effect on firm value partially. Furthermore, dividend policy is unable to moderate the relationship between tax avoidance and firm value. This finding implies that tax efficiency strategies through tax avoidance have not been perceived by the market as a positive signal for increasing firm value, and dividend policy has not played a role as a reinforcement in this relationship.